2018
DOI: 10.1098/rspb.2018.0845
|View full text |Cite
|
Sign up to set email alerts
|

The biomechanics of foraging determines face length among kangaroos and their relatives

Abstract: Increasing body size is accompanied by facial elongation across a number of mammalian taxa. This trend forms the basis of a proposed evolutionary rule, cranial evolutionary allometry (CREA). However, facial length has also been widely associated with the varying mechanical resistance of foods. Here, we combine geometric morphometrics and computational biomechanical analyses to determine whether evolutionary allometry or feeding ecology have been dominant influences on facial elongation across 16 species of kan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 42 publications
5
67
0
Order By: Relevance
“…This posits that closely related mammals tend to have longer rostra and narrower zygomatic arches as they increase in size [49,50], in a pattern that closely resembles what we found in wombats without allometry. CREA was suggested for kangaroo crania [18], but contested in a slightly different sample and landmarking protocol of kangaroos [23,24]. Instead, the authors postulated that a CREA-like pattern is not allometric and instead purely due to biomechanics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This posits that closely related mammals tend to have longer rostra and narrower zygomatic arches as they increase in size [49,50], in a pattern that closely resembles what we found in wombats without allometry. CREA was suggested for kangaroo crania [18], but contested in a slightly different sample and landmarking protocol of kangaroos [23,24]. Instead, the authors postulated that a CREA-like pattern is not allometric and instead purely due to biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…Suggestions of a constraint on marsupial skull shape through static allometry are at odds with several geometric morphometric studies that show only low or moderate levels of static allometry in marsupial crania [15,[20][21][22]. Two recent studies on kangaroos even suggested that allometry plays a lesser role in shaping cranial variation in this group, instead positing fast adaptation or individual developmental plasticity of the masticatory apparatus as the main driver [23,24]. This is consistent with suggestions that masticatory biomechanics may impact individual cranial shape to such a degree that developmental constraints either do not contribute much to within-species shape variation, or can be obscured by individual differences in mastication due to the bone's plastic response to mastication stresses [6,[25][26][27].…”
Section: Introductionmentioning
confidence: 98%
“…Though it has been suggested that this approach may bias studies toward recovery of the CREA pattern (Linde-Medina 2016), we use centroid size here in accordance with Tamagnini et al (2017) and Cardini (2019), who find it to correspond well with other methods of measurement. This also allows for more direct comparability with previous mammalian studies (Cardini and Polly 2013;Cardini et al 2015;Tamagnini et al 2017;Mitchell et al 2018;Cardini 2019). To investigate whether nonmammalian synapsid groups share a common allometric pattern, we performed a phylogenetic generalized leastsquares (PGLS) regression with a Brownian motion model of evolution using the geomorph function procD.pgls on a data set including all species in our study and using our concatenated supertree.…”
Section: Analysis Of Allometrymentioning
confidence: 99%
“…This posits that closely related mammals tend to have longer rostra and narrower zygomatic arches as they increase in size [59], in a pattern that is highly similar to the one we found within wombats but without allometry. CREA was suggested for kangaroo crania [18], but contested in a slightly different sample and landmarking protocol of kangaroos [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Suggestions of a constraint on marsupial skull shape through static allometry are at odds with several geometric morphometric studies that show only low or moderate levels of static allometry in marsupial crania [15,[20][21][22]. Two recent studies on kangaroos even suggested that allometry plays a lesser role in shaping cranial variation in this group, instead positing fast adaptation or individual developmental plasticity of the masticatory apparatus as the main driver [23,24]. This is consistent with suggestions that masticatory biomechanics may impact individual cranial shape to such a degree that developmental constraints either do not contribute much to within-species shape variation, or can 5 be obscured by individual differences in mastication due to the bone's plastic response to mastication stresses [6,[25][26][27].…”
Section: Introductionmentioning
confidence: 98%